Physical, Mechanical, and Chemical Characterization of Two Sympodial Bamboos (Gigantochloa Ligulata & Gigantochloa Scortechinii) & Their Potential for Construction Purpose - Ng, Kah Hoe (Universiti Sains Malaysia, 2022)
Non-traditional lignocellulosic resources, such as bamboo, may be converted into high-value products by utilizing efficient, low-cost, and low-pollution fractionation techniques. The purpose of this study is to determine and compare the physical, mechanical, and chemical characteristics between two bamboo species – Gigantochloa Ligulata and Gigantochloa Scortechinii – as a rapidly increasing resource of major regional relevance. The moisture content, tensile strength, compressive strength, antidecay characteristics, chemical resistance, NaOH solubility, and benzene-ethanol solubility of the samples were determined. This research demonstrates that in terms of compressive strength, bamboo Gigantochloa Ligulata is higher than bamboo Gigantochloa Scortechinii. So, bamboo Gigantochloa Ligulata is more potential to be the building material that always be compressed as the reinforcement of concrete that supports the whole building. In contrast, bamboo Gigantochloa Scortechinii has higher tensile strength than bamboo Gigantochloa Ligulata. Therefore, it is more potential to be the building material that requires to sustain higher tension force. Based on the experiment, it also showed that bamboo in dry condition is always stronger than the bamboo in wet condition. In addition, the higher benzene-ethanol extractives of the bamboo Gigantochloa Ligulata could be an advantage for anti-decay in architecture processing and utilization compared to bamboo Gigantochloa Scortechinii. Finally, bamboo after alkaline treatment will experience damage of fiber structure and then the strength will be decrease significantly as well. However, different bamboo species has different effect of alkaline treatment as well as the alkaline concentration.